Japan society - Shepherd, Greg; Appleseed Productions (New York, NY : [Distributed by] Insight Media, 1995, 1995)
Documentary examines Japanese society, including sports, family life, males and females, courtship, marriage, religion, education, work and government
Title from container
Editor, Shane Fincke
DVD format
Keywords: Japan -- Social life and customs; Japan -- Social conditions -- 1945-